Nilai Uji Rendam (Immersion Test) Dari Material Recycle Asphalt Pavement (RAP) Dengan Menambahkan Oli Bekas Pada Perkerasan Jalan - Saleh, Alfian; Wahyuni Megasari, Shanti; Lubis, Fadrizal; Trisep Haris, Virgo (Universitas Lancang Kuning, 2024)
Reclaimed Asphalt Pavement (RAP) is the result of dredging the old road pavement which is usually used as backfill and has even become waste that is usually rarely used. RAP material that is no longer used can be used as an additive in the manufacture of new asphalt concrete with rejuvenator. This study aims to determine the durability of used motor vehicle oil as a rejuvenating agent for RAP on the Lataston mixture gradation (HRS-WC) on Marshall and IRS characteristics. The testing stage is to test the characteristics of the RAP material. The optimum asphalt content (KAO) for the aggregate was obtained at 7,24%, while the optimum used oil content was obtained at 4,94% by weight of asphalt as a RAP rejuvenator. Marshall and IRS characteristics testing are in accordance with the 2018 Highways specification. Marshall test results show that as the amount of used oil freshener is added, the ability of the mixture to withstand loads decreases and the flexibility of the mixture increases, resulting in reduced asphalt durability represented by testing IRS 30 minutes and 24 hours which showed the durability value obtained a value of 60,49% in the Lataston mixture. As a result, the IRS value does not meet the requirements of the 2018 Highways Specification of 90%, so it is concluded that the results of the tests carried out do not meet the durability requirements and cannot be applied in the field..